2014
DOI: 10.7314/apjcp.2014.15.14.5607
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Breast Cancer Screening via Text Messages as Part of Continuing Education for Working Nurses: A Case-control Study

Abstract: Introduction: Although continuing education is necessary for practicing nurses, it is very difficult to organize traditional classes because of large numbers of nurses and working shifts. Considering the increasing development of mobile electronic learning, we carried out a study to compare effects of the traditional face to face method with mobile learning delivered as text messages by cell phone. Materials and Methods: Sixty female nurses working in our hospital were randomly divided into class and short mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 18 publications
0
31
0
1
Order By: Relevance
“…International studies have shown that the increased knowledge of nurses is associated with their professional experience and completion of courses after undergraduate training, and stress the importance of professional training and constant updating of knowledge for effective control of mammary tumors (16)(17)(18) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…International studies have shown that the increased knowledge of nurses is associated with their professional experience and completion of courses after undergraduate training, and stress the importance of professional training and constant updating of knowledge for effective control of mammary tumors (16)(17)(18) .…”
Section: Discussionmentioning
confidence: 99%
“…International studies on mammography affirm that a satisfactory relationship between professionals and users of health services is essential for adherence to breast cancer screening exams, and that the quality of the care provided by nurses is important to motivate adherence by female public health users to these exams (17)(18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 About 98% of sampled healthcare workers in Kenya owned mobile telephones, 8 and training delivered via SMS has led to improved nurse adherence to guidelines in that country and several other African projects. 9,10 SMS-based training interventions have also shown retention of knowledge scores equivalent to didactic teaching at 30 days, 11 while an improved adherence to guidelines was sustained at 6 months post the original intervention in a project in Kenya. 12 In rural South Africa a group of nurses reported several 'organically grown' mobile-telephone-based practices facilitating learning, including reflective practice, emotional support and teaching in unpredictable situations.…”
Section: Introductionmentioning
confidence: 99%
“…13 The success of mLearning in the developing world has been well documented in African rural healthcare workers treating infectious diseases, 9,10,12 but only one study, on nurses screening for breast cancer in Iran, was found in a hospital-based setting. 11 Documentation of its efficacy in an African hospital-based scenario was not found and it has not been proved in anaesthesia nurses. This study attempts to validate the use of SMS as a training tool for hospital-based anaesthesia nurses.…”
Section: Introductionmentioning
confidence: 99%